Preparation and Properties of Biodegradable Film Composites Using Modified Cellulose Fibre-Reinforced with PVA. (29th January 2012) - Laxmeshwar, Sandeep S.; Madhu Kumar, D. J.; Viveka, S.; Nagaraja, G. K.
Abstract : Cellulose has a potential to become a key resource in the development of biodegradable film composites. In this work, cellulose was modified by using 2-(Trifluromethyl)benzoylchloride by base-catalyzed reaction. Modification of cellulose was confirmed by IR studies. The biodegradable composite films were developed by film casting method using modified cellulose with Poly(vinyl alcohol) in different compositions. The film composites were characterized by mechanical, moisture absorption, gas barrier, and biodegradable properties. Obtained films have shown transparency and flexibility and displayed good mechanical properties. Film composites also showed good biodegradability. Better barrier properties showed by film composites as the percentage of modified cellulose increased. This indicates the importance of modified cellulose as a reinforcing agent. After evaluating these properties of film composites, we came to conclusion that these biocomposites can be used to membrane and packaging applications.